ABO blood group does not influence Child‐Pugh A cirrhosis outcome: An observational study from CIRRAL and ANRS CO12 CIRVIR cohorts. (17th January 2022) - Ollivier‐Hourmand, Isabelle; Repesse, Yohann; Nahon, Pierre; Chaffaut, Cendrine; Dao, Thông; Nguyen, Thi Thu Nga; Marcellin, Patrick; Roulot, Dominique; De Ledinghen, Victor; Pol, Stanislas; Guyader, Dominique; Archambeaud, Isabelle; et al.
Abstract: Background and aims: Non‐O blood group promotes deep vein thrombosis and liver fibrosis in both general population and hepatitis C. We aimed to evaluate the influence of Non‐O group on the outcome of Child‐Pugh A cirrhotic patients. Methods: We used two prospective cohorts of Child‐Pugh A cirrhosis due to either alcohol or viral hepatitis. Primary end point was the cumulated incidence of 'Decompensation' at 3 years, defined as the occurrence of ascites, hydrothorax, encephalopathy, gastrointestinal bleeding related to portal hypertension, or bilirubin >45 μmol/L. Secondary end points were the cumulated incidences of (1) 'Disease Progression' including a « decompensation» or « the occurrence of one or more parameters » among: prothrombin time (PT) <45%, albumin <28 g/L, Child‐Pugh worsening (B or C vs A or B, C vs B), hepatorenal syndrome, and hepato‐pulmonary syndrome, (2) other events such as non‐malignant portal vein thrombosis (nmPVT), and (3) overall survival. Results: Patients (n = 1789; 59.9% Non‐O group; 40.1% group O) were followed during a median of 65.4 months. At 3 years cumulated incidence of Decompensation was 8.3% in Non‐O group and 7.2% in group O ( P  = .27). Cumulated incidence of Disease Progression was 20.7% in Non‐O group and 18.9% in group O ( P  = .26). Cumulated incidence of nmPVT was 2.7% in Non‐O group and 2.8% in group O ( P  = .05). At 3 years overall survival was 92.4% in Non‐O group and 93.4% in group O ( P  = 1). Conclusion: Non‐O group does not influence disease outcome in Child‐Pugh A cirrhotic patients. Clinicals trial number NCT03342170.